2023
DOI: 10.7759/cureus.41520
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod-Associated Macular Edema in the Treatment of Multiple Sclerosis

Asma A Khan,
Sai Dheeraj Gutlapalli,
Mehvish Sohail
et al.

Abstract: Multiple sclerosis is a neurological disorder categorized by inflammatory processes with a high prevalence worldwide. It affects both motor and sensory pathways and is also associated with the visual pathway. Fingolimod is a commonly used drug for relapsing-remitting multiple sclerosis. It is a sphingosine 1-phosphate modulator acting on its receptors for immune cell accumulation, neuronal function, embryological development, vascular permeability, smooth muscle cell function, and endothelial barrier maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…According to our analysis, the most common serious adverse events (SAEs) caused by all the S1PR modulators were associated with ocular events, which was consistent with previous safety data ( Khan et al, 2023 ; Li et al, 2023 ). Among the related IMEs, macular oedema was reported frequently.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to our analysis, the most common serious adverse events (SAEs) caused by all the S1PR modulators were associated with ocular events, which was consistent with previous safety data ( Khan et al, 2023 ; Li et al, 2023 ). Among the related IMEs, macular oedema was reported frequently.…”
Section: Discussionsupporting
confidence: 91%
“…Nearly all the approved MS disease-modifying therapies have demonstrated a treatment effect on brain atrophy, which could result in an increase in retinal volume. Additionally, macular edema is also associated with the fingolimod modulation of S1PRs on the action of tight junctions of the blood-brain barrier and neurons ( Khan et al, 2023 ). Coppes et al reported a patient clinically presented with bilateral blurred central vision, painless, and no eye pain with eye movement after 10 days of fingolimod treatment ( Coppes, Gutierrez, Reder, Ksiazek & Bernard, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…INFβ and glatiramer acetate have favourable safety profiles in the pediatric population, as no malignancies or life-threatening events were reported [45][46][47][48][49]63]. On the other hand, newer DMTs have a reported risk for malignancies and serious adverse effects, such as hepatotoxicity or life-threatening PML [51,77,83,85,94,95,106,[143][144][145]. The daily need for subcutaneous drug administration for INFβ and glatiramer acetate is particularly distressing in both the pediatric and adolescent population and could lead to poor treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that leukopenia and lymphopenia, as a result of fingolimod's mechanism of action, increase infection risks [51]. Looking at the literature data of both POMS and AOMS treatment groups of fingolimod, several adverse effects are reported only in adults, such as melanoma, breast cancer, and macular edema [77].…”
Section: Fingolimodmentioning
confidence: 99%